The structure of the human temporomandibular joint disc: A scanning electron microscopy study - Minarelli, Ana M. [UNESP]; Del Santo Jr., Marinho; Liberti, Edson A. (My University, 1997)
The articular disc of the temporomandibular joint was studied in fetuses (16 to 39 weeks of intrauterine life), infants (up to 4 months of age), dentulous adults (aged 30 to 39 years), and completely edentulous adults (aged 60 to 69 years) by scanning electron microscopy. The constituent bundles of collagen fibers were stratified and were oriented anteroposteriorly, laterolaterally, and obliquely in the middle portion of the disc. A ring of laterolateral bundles constituted the main feature of the thick posterior portion. In the anterior portion of the disc, the fibers were anteroposteriorly and obliquely oriented. On the superior and inferior surfaces of the disc, a thin layer of perpendicularly arranged collagen fibers covered the underlying, thick, laterolateral oriented collagen fibers.
Keywords: Articular disc; Collagen fibers; Human temporomandibular joint; Scanning electron microscopy; collagen; adult; aged; female; fetus; growth, development and aging; histology; human; infant; male; middle aged; mouth disease; newborn; pathology; scanning electron microscopy; temporomandibular joint; ultrastructure; Adult; Aged; Collagen; Female; Fetus; Humans; Infant; Infant, Newborn; Male; Microscopy, Electron, Scanning; Middle Aged; Mouth, Edentulous; Temporomandibular Joint Disk